The pentacene films on the glass/ITO surface: structure and optical properties. (13th August 2018) - Sagan, P.; Aksimentyeva, O.; Wisz, G.; Tsizh, B.; Virt, I.; Rudy, I.; Fruginsky, M.
Abstract: The structure, morphology and optical transmittance spectra of pentacene films on the (glass/ITO) surface were studied. The films were grown by two methods - the thermal vacuum deposition (TVD) and pulsed laser deposition (PLD). The electron diffraction pattern from thermally deposited pentacene films confirms their polycrystalline structure while the diffraction pattern of PLD-coated layers has a diffusion character. The results obtained showed that layers deposited by the TVD method has an optical spectrum that is characteristic for the pentacene film in contrary to the layers deposited by the PLD method. It is found a sensitivity of the optical transmittance of pentacene films to the ammonia action, which may be used for development the optical gas sensor.